Optimizing Tilapia Hatchery Systems with Good Fish Breeding Practices (CPIB) in Lingsar District, West Lombok - Affandi, Rangga Idris; Abidin, Zaenal; Scabra, Andre Rachmat; Chen, Peter; Setyono, Bagus Dwi Hari; Dwiyanti, Septiana; Alim, Sahrul; Sumsanto, Muhammad; Diamahesa, Wastu Ayu; Asri, Yuliana (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Embung Pas Hamlet in Sigerongan Village, Lingsar District, West Lombok Regency, has quite large aquaculture potential, especially for tilapia commodities. However, in practice, tilapia fish breeder still faces various obstacles such as the less-than-optimal productivity of tilapia fry produced. Lack of understanding of the standards for Good Fish Breeding Practices (CPIB) is one of the main factors that hinders increased productivity and sustainability of hatchery businesses. This community service activity aims to improve the understanding and skills of tilapia fish breeder in Embung Pas Hamlet in applying the principles of CPIB. The implementation method includes counseling, discussion, and direct assistance with a participatory and demonstrative approach. Evaluation is carried out to measure changes in participants' knowledge and attitudes before and after the activity. The results of the activity showed a significant increase in understanding and technical skills of breeding related to aspects of biosecurity, water quality management, proper use of feed, and management of aquaculture waste. The participants also showed enthusiasm and commitment to implementing CPIB in their daily activities. This activity also encourages collective awareness of the importance of quality standards in sustainable hatchery. In conclusion, CPIB training and mentoring have a positive impact on increasing the capacity of fish breeder in Embung Pas Hamlet and have the potential to become a model for sustainable and competitive fisheries community empowerment.